Analysis of Flood Discharge due to Impact of Tropical Cyclone - Denik Sri Krisnayanti; Philipi de Rozari; Vilkanova C. Garu; Alvine C. Damayanti; Djoko Legono; Hamdan Nurdin (Civil Engineering Journal, 2022)
Tropical Cyclone Seroja, which occurred between April 2 to 6, 2021, is one of the strongest storms ever in East Nusa Tenggara. The track results of the cyclone showed that Seroja, formed at coordinates 10.5° S and 123° E, moved towards west longitude to Sumba Island and continued towards Australia. Moreover, the Global Precipitation Measurement (GPM) output was used to analyze the rainfall conditions at the center of the Seroja cyclone through the Kambaniru watershed in East Sumba, and the results showed that the precipitation continued to increase during Seroja's development to reach 225 mm. Therefore, this study aimed to analyze the effect of the rainfall during the storm on the maximum runoff experienced in the Kambaniru watershed through the application of quantitative analysis on the rainfall data from GPM data. The process involved analyzing the flood discharge using the HSS-SCS Curve Number method and GPM data, which were initially used to evaluate the rainfall during the TC Seroja due to limited field data. The results showed that the CN value in the Kambaniru watershed was in the AMC III condition with a curve number of 88.90 and the maximum flood during the Seroja storm was recorded to be 2,987 m3/s which is higher than the flood discharge for the 500 year return period. It was also discovered that the narrowing of the river channel on the Kambaniru Bridge section contributed to the collapse of the bridge. Doi: 10.28991/CEJ-2022-08-09-01 Full Text: PDF